Evaluasi Penerapan Booklet dan Edukasi Apoteker pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Mayapada Tangerang - Sagala, Radoti Merlin; Arozal, Wawaimuli; Sauriasari, Rani; Keban, Sesilia (Pharmaceutical Sciences and Research, 2018)
Type 2 diabetes mellitus is a degenerative disease with long-term treatment that requires knowledge and self-management to control blood sugar level. The purpose of this study was to evaluate the provision of booklet and pharmacist education in improving knowledge and behavior of self-management of type 2 diabetes mellitus patient at Mayapada Hospital Tangerang. This study respondents were 90 people who were divided into 3 groups. Group 1 got booklet and education, group 2 got booklet only and control group did not get any treatment. Fasting Blood Glucose (FBG) levels before the intervention were in poorly controlled category and after intervention there was no significant change. There was an increase in the level of knowledge and self-management in group 1 and group 2. There was no significant change in FBG. Provision of booklet with education by pharmacist showed a higher increase in knowledge (p=0.02) and self management behavior (p<0.001) than provision of booklet only. There was no relationship between knowledge and self-management behavior with blood sugar levels. It could be concluded that booklet and education by pharmacist could improve knowledge and behavior of self-management of DM type 2 patients in each intervention group. However, there was no relationship between knowledge and self-management behavior with FBG.